Management of Groundwater Quality in Sodic Soils using Semianalytical One-dimensional Solute Transport Model - Garg, Sunil; Shakya, S K; Bhardwaj, Anil (Journal of Agricultural Engineering, 2011)
A semi-analytical one-dimensional solute transport model to manage and predict groundwater quality was tested for its application in Golewala, Punjab. The model being semi-discrete and continuous in time has significant computational advantage over the existing ones, especially for long-term predictions. The model was tested for transport of soluble Ca + Mg, CO3 and HCO3 and EC in soil profile with respect to time under barren soil. The results showed that the model can be used to predict the status of total salt concentration at different depths with time and to manage ground water quality in sodic soils.